Necesidad de crear un periódico comunitario para la parroquia Guadalupe del cantón Zamora - Lupercio Sarango, Alcibar Omar (2015)
This research is called: "Need to create a community environment in the parish Guadalupe Region Zamora, period September 2013 to September 2014," evidenced the need for community media to disseminate the needs of people based on the needs that are aimed at encouraging participation through education. Discussing the topic methods, materials, techniques and instruments are used to delimit the topic to investigate. By applying the methodology, specifically through the survey the general and specific objectives that marked the investigative work, establishing conclusions and recommendations based on field work done verified. The inhabitants of Guadalupe parish provided the information necessary to specify the information in the problem and accurate data for the proposed approach. To provide a solution to the issue of research an alternative proposal, the creation of a community newspaper, "The Voice of the People" will be called, will be administered by the Vestry of Guadalupe parish, canton Zamora arises. The community newspaper aspires to become an alternative and friendly environment that promotes participation, and improve the integration of the peoples who seek to solve their problems.